Jurnal akuntansi & auditing Indonesia: LIKUIDITAS SAHAM, KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN - Mursalim (akuntansi UII, 2011)
The objective of the paper is to investigate the effects of stock liquidity, dividend policy by the proxy of dividend payout ratio, and dividend policy by the proxy of dividend yield to the value of the firm. The research tested the hypotheses by using multiple regression. Hypotheses’ testing was conducted by using research sample of 25 banking company registered in the Indonesian Stock Exchange during the years of 2006-2008